Capabilities for epistemic liberation: the case of hermeneutical insurrection of the Network of Community Researchers in Medellin, Colombia - Vargas, Monique Leivas (Journal of global ethics, 2023)
Community leaders in Colombia have historically suffered processes of microaggressions and intimidation that threaten the free exercise of their voice in the processes of production of knowledge and in the participation of the planning of their territories. In this article, we explore the case study of the Network of Community Researchers (NCR), also known in Spanish as Red de Investigadores Comunitarios, promoted by the University of Antioquia, Colombia. The NCR is a commitment to the co-production of knowledge about human security from below between community researchers and academics. This article analyses the contribution of the NCR to the human security of Medellin and a specific collection of capabilities for epistemic liberation of community researchers: the capability to be recognised as a producer of valid knowledge, to do through communicative openness, to learn from collective knowledge and to transform through collective action. The expansion of these four capabilities evidence processes of resistance and hermeneutic insurrection of some community leaders and activists who participate in the NCR. The analysis shows the contribution of the NCR to facilitate and generate a safe space in which community researchers communicate knowledge and practices and share experiences, risks, struggles, fears and collective dreams of transformation.